Risk, exposure and vulnerability to flood hazards in a rapidly developing country: the case of Peninsular Malaysia - Chan, Ngai Weng (Universiti Kebangsaan Malaysia, 1996)
Peninsular Malaysia is rapidly industrialising in recent decades and economic growth rates in recent years suggest that it will continue to do in the short to medium term. The pace of social, economic and political change is fast, as is the pace of technological change. Since independence, rapid economic development in agriculture, mining, industries and urbanisation (as well as other fields) has changed much of the natural system. Other things being equal, these developments have significantly contributed to disturbed hydrological regimes and other parameters relating to flood occurrences. Flood hazards are, therefore, being reinforced and perpetuated largely through human interference which can lead to their amplification. Rapid economic developments and the current push by the Malaysian government to attain the `newly industrialised country' status are described as rapidly changing contexts. As these contexts change, natural/physical systems are affected and they change accordingly. Such changes have given rise to increased flood risk, exposure and vulnerability amongst those living on floodplains.